Exploring the Impact of an AVRS Curfew Program on Recidivism of Juvenile Probationers in Korea - Cho, Younoh (International journal of offender therapy and comparative criminology, 2018)
Community corrections agencies across the world have adopted biometric technologies as a security tool and cost-effective monitoring strategy. This study investigates the effectiveness of the automated voiceprint recognition supervision (AVRS) curfew program for 386 Korean juvenile probationers from the Seoul Probation Office. Although the AVRS curfew program in Korea has been in effect for more than 14 years, effectiveness of the program has not been fully tested. A propensity score analysis was conducted to assess the effectiveness of the AVRS program, controlling for potential covariates of referring juveniles to the program. Contrary to expectations, a logistic regression analysis demonstrated that the innovative curfew program is a statistically significant factor in increasing the odds of recidivism. The article concludes with a discussion of implications for court-ordered juvenile curfew programs.